Zeta Potential Measurement Using Streaming Potential in Porous Media - Thanh, Luong Duy; Sprik, Rudolf (VNU Journal of Science: Mathematics - Physics, 2015)
Electrokinetic phenomena are induced by the relative motion between a fluid and a solid surface and are directly related to the existence of an electric double layer between the fluid and the solid grain surface. Electrokinetics in porous media plays an important role in geophysical applications and environmental applications. The zeta potential is one of the key parameters in electrokinetics. The zeta potential of liquid-rock systems depends on many parameters such as mineral composition of rocks, fluid properties etc. Therefore, the zeta potential is different for various rocks and liquids. In order to measure the zeta potential for fluid saturated porous rocks, streaming potential measurements have been carried out for 8 consolidated samples including natural and artificial rocks saturated with 7 different NaCl solutions. The measured zeta potential is then compared to previously published data for silica-based rocks. The comparison shows that the zeta potential is in good agreement with the experimental data reported in the literature. The results also indicate that the zeta potential depends not only on the electrolyte concentration but also on types of rock. Keywords: Streaming potential, zeta potential, electroosmosis, porous media, rocks.